ANALISIS KEKUATAN PAPAN PARTIKEL DARI SERAT AMPAS TEBU DENGAN PENAMBAHAN RESIN POLYESTER UNTUK PEMBUATAN PAPAN SKATEBOARD - Ikhsan, Dody; Rasid, M.; HB, Indra (MACHINERY Jurnal Teknologi Terapan, 2021)
Composites are materials that are formed when two or more different components are combined (Kroschwitz, 1987). K. Van Rijswijk et al in their book (Natural Fiber Composites, 2001) describes a composite is a hybrid material made of fiber-reinforced polymer resin, combining mechanical and physical properties. Research on the strength analysis of particle board by utilizing bagasse so that it has a better economic value. Variations in the ratio of fiber fraction and polyester resin were 2:40, 5:40 and 8:40 with each and mixed based on the ratio of fiber weight fraction and resin weight. Based on the analysis using ANOVA, it was found that the best composition of the final composite product was in the composition of 8 grams of bagasse fiber and 40 ml of polyester resin. The composition has a bending strength of 9, 19 N / mm2. Based on the analysis using ANOVA, it was found that the optimization parameters were 0.04 millimeter layer thickness and 16 seconds lighting time, the optimal results were in the dimensions of 40.01 millimeters in diameter and 3.20 millimeters of thickness.